PERANCANGAN INFOGRAFIS ANIMASI PENYAKIT INFLUENZA DAN PENCEGAHANNYA DI PUSKESMAS BOJONG NANGKA KELAPA DUA TANGERANG BERBASIS VIDEO SCRIBE - Gea, Herman Jaya; Wahyuningsih, Sri; Pepi Permatasari (Yayasan Nuraini Ibrahim Mandiri, 2024)
The Influenza disease is not well-known and understood by the people in Indonesia, especially in the Bojong Nangka area of Kelapa Dua district, Tangerang Regency. This year, there has been an increase in the number of cases of this health issue throughout Indonesia. Various forms of socialization about what Influenza is, how to prevent and treat it, have been conducted at the Bojong Nangka Health Center, but these activities have not shown satisfactory results. To achieve the goal of better informing and educating the wider population about Influenza and its prevention, the author is interested in conducting research on this issue using data collection research methods including direct observation, interviews, literature reviews, and designing a video using Video Scribe. The aim is to create a new information medium that is more effective in providing or disseminating information and knowledge to the wider public. This will help remind people about Influenza and its prevention methods. Keywords: Design, Health Center, Animated Infographics, Video Scribe, Influenza.